Assessment of the anti-HBs antibody response in Beninese infants following 4 doses of HBV vaccine, including administration at birth, compared to the standard 3 doses regime; a cross-sectional survey. Issue 7 (11th February 2020) - Accrombessi, Manfred; Adetola, Crepin Victor; Bacharou, Salwane; Dossou, Yannelle; Avokpaho, Euripide; Yakoubou, Annatou; Koumakpai-Adeothy, Sikiratou; Lozes, Evelyne; Issifou, Saadou
Abstract: Hepatitis B virus (HBV) infection remains one of the major neglected health issues worldwide. In sub-Saharan Africa (SSA), HBV endemicity is high, with more than 8% of the population being chronic HBV carriers. Recently, WHO recommended that all infants should receive their first dose of the HBV vaccine as soon as possible after birth. Unfortunately, the incorporation of a birth dose of HBV in the expanded programme immunization (EPI) has not occurred in the majority of countries in SSA. From April to September 2017, a cross-sectional survey was conducted in two vaccine units located in southern Benin. We assessed the sustained anti-HBs antibody response in infants induced by a standard scheme of 3 doses of HBV vaccination (6, 10, 14 weeks) in comparison to a scheme of 4 doses with a birth dose included (0, 6, 10, 14 weeks). Blood samples were systematically collected in the first 140 children aged 9 months and their mothers who had consented to participate for the detection of HBs antigen and the quantification of anti-HBs antibodies. The prevalence of HBV infection among infants and mothers was 2.2% and 7.1%, respectively. Infants who received 4 doses of HBV vaccine had a significantly higher level of anti-HBs antibody than those who received 3 doses of vaccine (557.9 UI/L vs. 386.9 UI/L, respectively, P  = 0.03). We also showed that the scheme of 4 doses was associated with a significantly higher sustained protective response in comparison to the scheme of 3 doses (aOR 2.49, 95% CI 1.03–6.03, P  = 0.04). This result provides further evidence of the importance of administering HBV vaccine at birth, but also highlights the importance for the prevention of vertical transmissions. Additional studies are needed to better establish the cost-effectiveness of such a 4 doses immunization strategy before implementing the HBV vaccination at birth in the EPI.